Applying a landscape ecological approach and geodesign from a farmer-centric position to inform the creation of future multifunctional, sustainable agricultural landscapes : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Natural Resources Management at Massey University, Palmerston North, New Zealand - Tran, Duy Xuan (Massey University, 2023)
In the wake of environmental challenges, it is important to improve the environmental sustainability of farm systems and landscapes whilst ensuring profitability for the farmers that manage them. This PhD study draws on theories from landscape ecology and geodesign to plan and design multifunctional agricultural landscapes from a farmer-centric position with sustainability in mind. A hill country and steep-land farm in New Zealand is used as a case study. A conceptual framework is proposed to guide landscape planning. The framework applies an ecosystem-based management approach (i.e., ecosystem services approach) coupled with geodesign at the farm scale. A comprehensive spatially explicit assessment of landscape multifunctionality and associated ecosystem services at the farm scale is carried out to understand the spatial variation of ecosystem services provision and how land use and land management goals of the landowners reflect the value and quality of landscape multifunctionality. Afterwards, spatially detailed variations in the relationship between landscape structure and the provision of ecosystem services is quantified to understand how landscape structure can affect the provision of ecosystem services in the farmed landscape. Finally, collaboration with the case farmers and application of different tools and models are carried out to generate future land use and management scenarios for the case study farm, visualise changes, and assess the impacts of future land use on landscape multifunctionality and the provision of associated ecosystem services and economic outcomes. This helps to demonstrate how the proposed approach can be applied to plan and design multifunctional agricultural landscapes that offer improved sustainability in the NZ hill country farmed landscapes. The results from the case study suggest that the proposed approach provides an effective solution for sustainable farm system design and that it can make an important contribution to advancing environmental management in New Zealand, as well as in other countries which face similar issues.
Keywords: Sustainable agriculture; Ecosystem services; Landscape design; Natural resources; Management; Hill farming; New Zealand; 410406 Natural resource management